(untitled) (Third Sector Social Economic Review, 2025)
Rural development refers to enhancing the contribution of rural areas to the local and national economy and improvement of the socio-economic conditions of rural dwellers. Academic studies reveal the need for rural development in Türkiye. The question of what measures should be taken to ensure rural development remains current. This study addresses the Boğatepe village of Kars, which recently gained attention in rural development in Türkiye. It aims to explore how the unique development factors in the village influence sustainable development. It utilized qualitative research methodology. The village’s socio-cultural and economic elements were examined, and in-depth interviews were conducted with individuals who observed these values and development processes firsthand. The findings, derived from relevant literature and research, indicate that the village’s strong culture of solidarity significantly impacts its economic landscape. Local resources, association activities, training sessions, and entrepreneurship initiatives are crucial in unlocking its potential. Elements such as ecotourism and cheese production contribute to the advancement of the community. Furthermore, the study concluded that the development elements of Boğatepe village can be shown as an exemplary development model for villages with similar characteristics in Turkey.